HUBUNGAN CYBERBULLYING DENGAN RISIKO IDE BUNUH DIRI PADA REMAJA - Heni Aguspita Dewi; Suryani Suryani; Aat Sriati (Jurnal Keperawatan Padjadjaran, 2023)
Background: Cyberbullying is a serious problem experienced by almost all countries. In Indonesia, the highest internet users are adolescents, so that adolescents are at risk of experiencing cyberbullying. Cyberbullying is bullying that is done through social media. Bullying carried out both traditionally and through social media has a psychological impact in the form of feelings of sadness and suicide attempts. Purpose: to determine the relationship between cyberbullying and the risk of suicidal ideation in adolescents. Methods: this study was a correlational study with a cross-sectional approach of 1.043 students from ten state high schools and four state vocational schools with random sampling. Data analysis used the Chi-Square test, Kruskal-Wallis test, and Mann-Whitney test. Results: As many as 21.0% of adolescents involved in cyberbullying are at risk of suicidal ideation. There is a relationship between cyberbullying and the risk of suicidal ideation in adolescents p = 0.000 (p <0.05). Conclusions: The risk of suicidal ideation is not only for adolescents who are involved as victims of cyberbullying but also affects adolescents who are involved as perpetrators, both perpetrators and victims.